COMUNIDADE DE NEMATOIDES ASSOCIADOS A LAGARTOS DO PARQUE NACIONAL DA SERRA DA CAPIVARA, NORDESTE DO BRASIL. - VELOSO, Gustavo de Macedo (2020)
This study sought to describe the nematode fauna associated with lizards from the Caatinga biome, Northeastern Brazil. The first chapter makes a general presentation about parasitism, showing the ecological and evolutionary factors that allow the parasite-host relationship. The second chapter describes the first parasitic sampling of the lizard Tropidurus helenae and analyzes the similarity of the nematode fauna of this species with other lizards of the Tropiduridae family sampled in Brazil. The results show T. helenae presenting a greater wealth of nematodes and a higher value of general prevalence when compared to other similar lizards that integrate the same group (T. semitaeniatus). The nematode fauna of T. helenae was more similar to the fauna of the counterpart T. hispidus from the Caatinga and Atlantic Forest areas. The phylogenetic and geographical distance could not be used as an explanatory standard for the observed similarity. In the third chapter, we verify the influence of biological and ecological characteristics of hosts and parasites on nematode aggregation levels. In addition, the influence of ecological and historical factors on the structure of the parasitic community was evaluated. As for the results, the aggregation levels reported by the Average Variance Ratio were positively influenced by the hosts' body mass. Larger mass lizards provide a greater amount of niches and space for parasites to attach, in addition, larger lizards are probably older, which contributes to a greater accumulation of parasites. The parasite community presented a structure and this was partially explained by phylogeny, revealing a significant historical effect on the distribution of pharyngodonid nematodes in their respective hosts. This distribution derives from a history of coevolution with its hosts, reflecting a common ancestry and a phylogenetic adjustment.